Masculinization of Nile tilapia fry (Oreochromis niloticus) with the aromatase inhibitor letrozole - Vega Galarza, Elsa (2021)
This paper presents the results of two experiments for the masculinization of tilapia fry (Oreochromis niloticus) through the use of an aromatase inhibitor, letrozole, administered in fish feed. The first experiment evaluated the effect on growth, survival, and the percentage of masculinization of sexually undifferentiated fish undergoing letrozole doses of 50 (T1), 100 (T2), and 200 (T3) mg kg-1 during four weeks. There was a negative control group (C0) feed without letrozole and a positive control group (C) that received 60 mg kg-1 of 17 alpha-methyltestosterone (MT) in feed. No significant differences in growth (weight and length) and survival were found between treatments and control groups. Treatments T1, T2, T3 showed a percentage of 90%, 100% and 93% of males, not showing significant differences. It was found 66% of males in group C and 45% in group C0, showing significant differences between each other and with respect to all letrozole treatments. It was found 3% of females in T1 and 7% of fish with intersex gonads in both T1 and T3. In the second experiment, the fishes were feed a dose of 50 mg kg-1 of letrozole during two weeks (2S) and three weeks (3S). The results were 73% of males for 2S and 82% for 3S, showing significant differences. It is concluded that letrozole in doses between 50 and 200 mg kg-1 achieves the masculinization of more than 90% of the O. niloticus fry, after 4 weeks of treatment without affecting survival and growth